Analisis Pengaruh Motivasi Kerja, Disiplin Kerja, dan Kompensasi Terhadap Kinerja Karyawan pada CV. Siuk Body Repair - Daffa Adhipratama, Fahrizal; Kusdiyanto (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to analyze the effect of work motivation, work discipline, and compensation on employee performance. By using a quantitative approach. The population in the study were all workers at Cv. Siuk Body Repair and the research sample was 50 employee taken with saturated sampling technique. The data analysis method used is data instrument test, classical assumption test, coefficient of determination test, t-test and f-test. Based on the results of hypothesis testing, it shows that partially motivation, discipline and compensation have a significant positive effect on the performance of employees of dicv siuk body repair. Based on the f test, the variables of motivation, discipline and compensation simultaneously have a significant positive effect on employee performance at dicv siuk body repair.